The study on the response of erosion and deposition evolution in the main channel of the Tarim River to water and sediment conditions under different representative years - Jiuzhou Gao; Lin Li; Quanli Zong; Wenhong Dai (PLoS ONE, 2025)
To investigate the impact of different water and sediment conditions on the morphological shaping of the middle reaches of the Tarim River, this study establishes an erosion-deposition evolution model for the Yingbazha to Wusiman River section under the 2018 shoreline conditions using MIKE21 software and conducts validation. Five working conditions were selected for typical years of high-flow, normal-flow, and low-flow, as well as years of extreme floods and extreme droughts, to simulate the river channel’s erosion and deposition evolution under varying water and sediment conditions. By analyzing metrics such as erosion and deposition volume, depth of scour and fill, changes in the channel’s planform morphology, thalweg elevation variations, and cross-sectional changes along the river reach, the patterns of erosion and deposition evolution in this segment were systematically examined. The results indicate that: (1) Under different representative year conditions, the river was always in a net deposition state. The sediment deposition was highest in the extreme flood year (1.885 × 10 7 tons, accounting for 34% of the incoming sediment) and lowest in the extreme drought year (1.109 × 10 6 tons, accounting for 83% of the incoming sediment). The unit runoff sediment transport efficiency increased by 54% with the increase in flow. However, when the runoff exceeded the critical threshold of 3.7 × 10 9 m 3 , the increase in scour volume (+440%) far outpaced the deposition volume (+143%), revealing a critical turning point in the erosion-deposition mechanism. (2) The erosion-deposition process follows a three-stage evolutionary pattern of “deposition-scouring-redeposition”: At low flow, insufficient sediment-carrying capacity leads to continuous deposition. After surpassing the critical flow, the sediment-carrying capacity dominates scouring. Under high flow conditions, the water and sediment volume increases sharply, restarting deposition. The deep pool elevation exhibits corresponding “rise-drop-rise” periodic fluctuations. (3) Through analysis of typical cross-sections, it is shown that in extreme flood years and typical wet years, the lateral swinging of the main channel causes scouring. However, the collapse of the bank and the widening of the river channel result in increased deposition in the main channel, leading to an overall elevation of the riverbed. In typical drought years and extreme drought years, due to lower flow, water levels, and flow velocities, the erosion-deposition process only occurs within the main river channel. The research results provide a better understanding of the erosion-deposition evolution trend of the meandering section of the Tarim River’s main channel, offering scientific guidance for the future development, management, and sustainable development of the middle reach of the Tarim River.